Tinjauan Tahap Pemanfaatan Pengelolaan Pulau Kecil (Studi Kasus Putusan PTUN Jakarta mengenai Reklamasi Pulau K) - Jati Pamungkas, Tegar; Vanisrooy, Gabriel Sanno; Meylani, Nur Anissa; Wibowo, Sulistyo (Universitas Islam Negeri Alauddin Makassar, 2023)
This article examines natural resources under the control of a country. Indonesia adheres to state property where natural resources are controlled by the state In accordance with Article 33 paragraph (3) of the 1945 Constitution. State control aims to create justice for citizens Indonesia. This article uses a qualitative method as a research method using a normative juridical approach. In compiling articles, the authors collect data using literature studies. This study aims to discuss the concept of the state in managing coastal areas and small islands along with an analysis of K Island reclamation decisions in Jakarta. This research resulted that the management of coastal areas and small islands is divided into three stages wherein the stages of planning, utilizing and supervising and controlling and the decision on the reclamation of K Island that the reclamation of K Island was canceled because it was not in the public interest.